Music-based interventions using digital technology for individuals with acquired brain injuries: a scoping review - Yu, Huiyuan; Lu, Xin; Kim, Soo Ji (Frontiers in Psychology, 2025)
BackgroundThe use of digital technology in music-based interventions for individuals with brain injuries has gained traction, especially post COVID-19, in addressing the need for effective, long-term rehabilitation. This scoping review examines the landscape of digital music-based interventions, focusing on their application in motor and cognitive rehabilitation for patients with brain injuries.MethodsWe conducted a literature search using five academic databases: PubMed, CINAHL, Medline, Google Scholar, and Web of Science. Twenty-six studies met the predefined criteria for inclusion in this review, and these studies were analyzed including digital interventions used.ResultsTwenty-six of 1994 studies were included. Results demonstrated a clear evolution in intervention methodologies, with earlier research focusing on rhythmic and MIDI-based tools, while more recent studies integrated virtual reality, augmented reality, and adaptive feedback mechanisms. The findings showed significant improvements in motor functions, such as upper limb movement and gait, in most of the reviewed studies, as well as some cognitive benefits, particularly when personalized music interventions were applied. However, challenges were noted regarding device complexity, cost, and inconsistent assessment methods across studies.DiscussionDigital music-based interventions show substantial promise in enhancing motor and cognitive function for individuals with neurological impairments. Nevertheless, barriers such as technological accessibility, the need for patient comfort, and a lack of standardization in assessment remain. Future research should focus on simplifying interfaces, standardizing protocols, and exploring hybrid interventions that combine immersive virtual reality with the adaptability of music therapy to create holistic, patient-centered rehabilitation solutions.